Effect of reflux ratio on nitrogen removal in a novel upflow microaerobic sludge reactor treating piggery wastewater with high ammonium and low COD/TN ratio: Efficiency and quantitative molecular mechanism. (November 2017) - Meng, Jia; Li, Jiuling; Li, Jianzheng; Deng, Kaiwen; Nan, Jun; Xu, Pianpian
Highlights: To treat piggery wastewater with high NH4 + density and low C/N ratio. An innovative upflow microaerobic sludge reactor was constructed. Effect of reflux ratio (RR) and mechanism of nitrogen removal were investigated. RR 34 was favorable for NH4 + and TN removal with anammox as the dominant mechanism. Decrease in RR stimulated ammonia-oxidization but inhibited anammox. Abstract: A novel upflow microaerobic sludge reactor (UMSR) was constructed to treat manure-free piggery wastewater with high NH4 + -N and low COD/TN ratio. In the light of the potential effect of effluent reflux ratio (RR) on nitrogen removal, performance of the UMSR was evaluated at 35 °C and hydraulic retention time 8 h with RR decreased from 45 to 25 by stages. A COD, NH4 + -N and TN removal of above 77.1%, 80.0% and 86.6%, respectively, was kept with a RR over 35. To get an effluent of TN not more than 80 mg/L with a TN load removal above 0.88 kg/(m 3 ·d), the RR should be at least 34. Real-time quantitative polymerase chain reaction of functional bacteria revealed that the RR of less than 34 stimulated ammonium oxidation but badly inhibited anammox, the dominant nitrogen removal pathway, resulting in the remarkable decrease of nitrogen removal in the reactor.